MELIHAT PEMANDANGAN KOTA DALAM FOTOGRAFI URBAN LANDSCAPE - Anin Astiti (Pendhapa, 2010)
Urban landscape is a term refers to something related to urban exploration. Urban itself means an area that has a function as a living area, the distribution centre that has its own governance, and an economic activity that is based not only on agriculture. It might be said that urban landscape photography showed an image from that area with the situation at the urban or suburban living area. By seeing the urban landscape photography we can see the record of happenings and atmosphere in the area which consists of streets, buildings, parks, and the infrastructures that support the people inside.Keywords: Seeing, Photography, Urban, Landscape.Â